The Antarctic and South American species of Deschampsia: phylogenetic relationships and cytogenetic differentiation. Issue 5 (4th July 2021) - González, María Laura; Chiapella, Jorge O.; Urdampilleta, Juan Domingo
Abstract : Deschampsia P. Beauv. is a cosmopolitan grass genus, which grows in cold and temperate regions, including about 15 species growing in South America and Antarctica. The species delimitation is difficult due to the high phenotypic plasticity and the likely occurrence of hybridization which generates species complexes with high morphological affinity. This work aims to describe the cytogenetic traits of the South American species of Deschampsia, highlighting similarities and differences in a phylogenetic context. We report the chromosome number of seven species of Deschampsia and Deyeuxia eminens for the first time, verifying that basic chromosome number x = 13 is shared by all the species. We found that the phylogenetic relationships are in agreement with the morphological affinities described in the species revisions, and the species of Deschampsia and Deyeuxia Sect. Stylagrostis form a well-supported clade. Despite the variation from x = 13 reported for populations of Deschampsia in the northern hemisphere, all the South American and Antarctic taxa studied here have a conserved basic chromosome number. Polyploids were found in several species, which suggests that genomic duplication is a recurrent process in the evolutionary history of Deschampsia. In contrast with the conserved chromosome morphology, the rDNA pattern showed high intra- and inter-specific variability and it is related to the phylogeny. Particularly, the complex of D. cespitosa is polymorphic for the distribution pattern of rDNA, as was also seen for molecular and morphological traits. Our results suggest that the common ancestor between Deschampsia and Deyeuxia sec. Stylagrostis could have had chromosomal characteristics currently shared by both. The incorporation of new chromosomal, molecular, and morphological data in Deyeuxia species will allow clarification of the close phylogenetic relationship with Deschampsia, in which reticulation and hybridization events cannot be excluded.